From Antigone to the respectable woman: L’immagine hegeliana della donna nella dialettica tra la Fenomenologia dello Spirito e la Filosofia del diritto del 1820 - Rózsa, Erzsébet (B@belonline, 2022)
The ‘proper’ woman is the protagonist of Hegel’s mature thought. Indeed, it has never stimulated him as much as Antigone. However, he still degraded Antigone: he undermined the uniqueness of the greatness of her character in the Phenomenology, mixed his image of Antigone with modern bourgeois features, and thereby transferred some characteristics of her uniqueness to the image of the woman in the context of the nuclear family in the emerging bourgeois society. This fused image of Antigone’s greatness damages her, and also does not facilitate an adequate interpretation and self-interpretation of women, or rather the clarification of their social and gender roles in the emerging modern society. Strictly deviating from this hybrid picture, Hegel’s Philosophy of Right has offered a comprehensible, and in many ways still relevant picture of the woman of the modernity, through differentiated social and gender roles suited to the expectations of the emerging modern society, that is through a corresponding self-interpretation and self-determination. A subjective-normative orientation in the practical attitude is likewise something women share with men: a woman must appropriate and exercise her social and gender roles properly. But all these expectations fall far short of Antigone’s greatness. Through his insight into the fragility of human existence in the modern age, Hegel opened up a perspective in which we, women and men, repeatedly interrogate the meaning of our own existence.